Explaining racial and ethnic inequalities in postpartum allostatic load: Results from a multisite study of low to middle income woment. (December 2016) - O'Campo, Patricia; Schetter, Christine Dunkel; Guardino, Christine M.; Vance, Maxine Reed; Hobel, Calvin J.; Ramey, Sharon Landesman; Shalowitz, Madeleine U.
Abstract: Background: Racial and ethnic inequalities in women's health are widely documented, but not for the postpartum period, and few studies examine whether neighborhood, psychosocial, and biological factors explain these gaps in women's health. Methods: Using prospective longitudinal data collected from 1766 low to middle income women between 2008 and 2012 by the Community Child Health Network (CCHN), we tested the extent to which adjustment for neighborhood, economic, psychological, and medical conditions following a birth explained differences between African American, Latina, and White women in an indicator of physiological dysregulation allostatic load (AL), at one year postpartum as measured by 10 biomarkers: Body Mass Index, Waist Hip Ratio, systolic and diastolic blood pressure, high sensitivity C-reactive protein, Hemoglobin A1c, high-density lipoprotein and cholesterol ratio, and diurnal cortisol. Results: Mean postpartum AL scores were 4.65 for African American, 4.57 for Latina and 3.86 for White women. Unadjusted regression estimates for high AL for African American women (with White as the reference) were 0.80 (SD = 0.11) and 0.53 (SD = 0.15) for Latina women. Adjustment for household poverty, neighborhood, stress, and resilience variables resulted in a reduction of 36% of the excess risk in high AL for African Americans versus Whites and 42% of the excess risk for Latinas compared to Whites. Conclusions: Racial and ethnic inequalities in AL were accounted for largely by household poverty with additional contributions by psychological, economic, neighbourhood and medical variables. There remained a significant inequality between African American, and Latina women as compared to Whites even after adjustment for this set of variables. Future research into health inequalities among women should include a fuller consideration of the social determinants of health including employment, housing and prepregnancy medical conditions. Highlights: We report on inequities in postpartum allostatic by race and ethnicity. We assessed whether psychosocial and economic factors explained inequalities. Economic and psychosocial factors explained 36–42% of race/ethnicity inequalities.